PENGARUH REPUTASI AUDITOR TERHADAP MANAJEMEN LABA DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI (PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Mulyono, Agus Tri (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACK The purpose of this study is to examine the effect of the auditor's reputation on earnings management and to examine the effect of the auditor's reputation on earnings management moderated by corporate governance. This study uses three control variables, namely firm size, leverage and market to book value. The data used in this study is secondary data derived from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2013-2015. By using purposive sampling, this study uses 109 sample companies with a period of 3 years, resulting in 327 years of observation. Data analysis method used in this research is Simple Linear Regression with Ordinary Least Squared (OLS) and Moderating Regression Analysis (MRA) approach. The results showed that the auditor's reputation had a significant negative effect on earnings management and Corporate Governance had no effect as moderator of earnings management. Of the three control variables used in this study, only leverage (DER) has an effect on earnings management, while the other two variables ie firm size and market to book value have no effect